Buku kedominikanan : SD kelas III-semester 1&2 /Emilia Ria Daniati, Robertus Widiarta ; editor, Sr. Serafine ; ilustrator, Tri Indriartanto, Gregorius Syarief, Thomas Sigit Budiawan - EMILIA RIA DANIATI; Robertus Widiarta; Serafine, Sr; Tri Indriartanto; Gregorius Syarief; Thomas Sigit Budiawan (St. Dominic Publishing, 2015)
x, 86 hlm. : ilus. ; 24 cm.